2011
DOI: 10.2967/jnumed.111.095257
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT for Monitoring Treatment Responses to the Epidermal Growth Factor Receptor Inhibitor Erlotinib

Abstract: Response rates of unselected non–small cell lung cancer (NSCLC) patients to the epidermal growth factor receptor inhibitor erlotinib are low and range from 10% to 20%. Early response assessments are needed to avoid costs and side effects of inefficient treatments. Here we determined whether early changes in tumor uptake of 18F-FDG can predict progression-free and overall survival in NSCLC patients who are treated with erlotinib. Methods Twenty-two patients (6 men, 16 women; mean age ± SD, 64 ± 13 y) with stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
103
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 29 publications
6
103
0
Order By: Relevance
“…Metabolic imaging of NSCLC and several other tumor types has been shown to be valuable in response assessment in the setting of targeted therapy (10)(11)(12)(13)(14). 18 F-FDG PET/CT provides information about tumor metabolic activity, which may be useful for monitoring molecular changes associated with the treatment response (15,16).…”
mentioning
confidence: 99%
“…Metabolic imaging of NSCLC and several other tumor types has been shown to be valuable in response assessment in the setting of targeted therapy (10)(11)(12)(13)(14). 18 F-FDG PET/CT provides information about tumor metabolic activity, which may be useful for monitoring molecular changes associated with the treatment response (15,16).…”
mentioning
confidence: 99%
“…Attenuated 18 F-FDG consumption was observed within hours of the combination treatment and could predict therapeutic outcome. Although clinical studies are beyond the scope of this review, they largely mirror what has been identified in preclinical studies: rapid changes in 18 F-FDG uptake-in some cases as early as 24-48 h after treatment-can predict a therapeutic response to oncogene-targeted therapy (23,24). Thus, 18 F-FDG PET may be particularly valuable for quickly evaluating whether a new therapy or therapeutic strategy that either directly or indirectly targets glucose uptake can elicit an important functional tumor response.…”
Section: Noteworthymentioning
confidence: 99%
“…Early FDG PET-CT after the start of erlotinib treatment identified patients who benefited from this targeted therapy (36). Thirty-four patients with untreated stage IV NSCLC were evaluated in this phase II trial.…”
Section: Functional Imaging For Response Assessment To Targeted Theramentioning
confidence: 99%